Adolescent pregnancy prevention in rural Indonesia: a participatory action research - Diyan Effendi; Lestari Handayani (deceased); Arief Nugroho; Iswari Hariastuti (James Cook University, 2021)
Introduction: Adolescent pregnancy remains a difficult problem in developing countries, including Indonesia. Pregnancy at an early age is a risk factor for maternal and infant mortality. A recent report indicates that adolescent pregnancy is even higher in rural areas. Therefore, this study aims to identify factors associated with adolescent pregnancy in rural Indonesia and formulate intervention actions to reduce the teenage pregnancy rate. Methods: Participatory action research (PAR) was conducted in the rural area of Mesuji District, Lampung Province, Indonesia. Six meetings, including four focus group discussions (FGDs), were held. The FGDs were audio-recorded and transcribed for inductive analysis. Themes emergent from the data were discussed with the local collaborators to achieve agreement. Results: Five factors were identified as determinants of adolescent pregnancy. They were low uptake of reproductive health services, low educational attainment, juvenile delinquency, poverty, and social and cultural norms. The intervention actions taken included income generation and reproductive health education. Discussion: This study verifies previous studies' findings that adolescent pregnancy determinants are mostly socioeconomic factors. These findings are essential because adolescents in this study setting endure significant disparities in health services and socioeconomic opportunities. Without sufficient intervention relating to these adolescents' needs and perceptions, the gap will continue to grow. Conclusion: Socioeconomic factors influence adolescent pregnancy. Cross-sectoral cooperation and active community participation are needed to address the problem. PAR is useful to explore the causes of health issues and promote active community participation.